Hydroxyapatite-based bone repair biomaterials based on clinical heterogeneity: modification strategies, performance regulation, and personalized repair pathways - Leiyun Huang; Jinghan Hu; Qingjin Cai; Jing Qian; Yuncheng Bai; Shangwei Wu; Yu Zhang; Yifan Wang; Hongrui Gao; Daiwei Wang; Zengdong Meng; Yongzhen Liu (Frontiers in Bioengineering and Biotechnology, 2026)
The repair of bone defects represents a major clinical challenge in orthopedics, oral and maxillofacial surgery, and trauma surgery. The heterogeneity of their etiology, anatomical sites, local microenvironments, and patients’ systemic conditions imposes diverse and sometimes contradictory performance requirements on repair materials. As the primary inorganic component of human bone, hydroxyapatite (HA) is considered an ideal foundational material for bone repair due to its excellent biocompatibility, osteoconductivity, and osteoinductive potential. However, its inherent brittleness, insufficient mechanical strength, and single functionality limit its application in complex clinical scenarios. This article reviews the latest advances in the modification of HA-based materials through strategies such as ion doping, composite reinforcement, structural regulation, and surface functionalization, aiming to precisely modulate their mechanical properties, degradation behavior, osteogenic activity, antibacterial capacity, and pro-vascularization functions. Furthermore, this article provides an in-depth analysis of the heterogeneous characteristics of various clinical bone defect types—including infectious, load-bearing, ischemic (insufficient blood supply), osteoporotic, and post-tumor resection defects—and their differential requirements for material performance. On this basis, a new clinical problem-oriented material design paradigm is proposed, shifting from a “universal” approach to a “personalized” one. This involves a personalized research and development strategy that conducts precise functional integration and performance trade-offs for specific clinical scenarios (e.g., “antibacterial-dominant,” “mechanical-bioactive synergy,” “osteogenesis/anti-resorption dual regulation,” “pro-vascularization induction,” and “integrated tumor suppression and repair”), thereby achieving a precise match between material properties and specific clinical needs. Finally, this article discusses the current limitations regarding the standardization of performance evaluation, multi-functional synergistic mechanisms, and clinical translation. It also anticipates future development directions for personalized bone repair materials, including the construction of a multi-scale and multi-dimensional material performance evaluation system, the advancement of “personalized responsive” material development, and the strengthening of clinical translation research.